Studies on Robotic Coding Education in Science Education: A Systematic Literature Review - Munise Seckin-Kapucu (Journal of Education in Science, Environment and Health)
This study aims to examine the methodological trends and findings in studies on robotic coding in science education published between 2015-2022 comprehensively and holistically. For this purpose, the articles related to the subject were systematically reviewed. In addition, web of Science and SCOPUS databases were scanned for keywords related to robotic coding, and 15 studies on robotic coding with full-text access were included in the analysis. The researchers prepared a data collection form to analyze the publications included in the research within the framework of the determined categories. Regarding the results of the review of robotic coding studies in science education, they mainly focus on cognitive skills, followed by applied studies in robotic coding teaching. The suggestions for future robotic coding studies in science education mainly involve applications and further research. Regarding applications, there are more suggestions for the integration of robotic coding. In this context, it was recommended to carry out studies that examine various 21st-century skills, integrate different disciplines, use different equipment, address psychomotor skills, and focus on curriculum development.